(untitled) (Research, Society and Development, 2021)
To demonstrate the importance of the 6-minute walk test (6MWT) to evaluate the cardiorespiratory responses induced by rehabilitation in patients who suffered a myocardial infarction and chronic obstructive pulmonary disease patients. The study was conducted in 3 stages, the first composed by the selection and sample evaluation through the 6MWT, the second by the cardiac rehabilitation period, and the third by the reevaluation of the sample, which was again tested on the 6MWT. Four individuals between 65 and 80 years old were evaluated and divided into 2 groups. Group 1 had a 6.46% increase in resting arterial pressure (p=0.13) and a 6.27% increase in peak arterial pressure (p=0.18), while group 2 had a 5.87% decrease in resting arterial pressure (p=0.20) and a 6.51% decrease in peak arterial pressure (p=0.22). The 6MWT is a qualified test to inquire about the improvement or the worsening of the patient’s hemodynamic part.